2016
DOI: 10.1021/acs.est.5b04958
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Aspects of the Interfacial Catalytic Oxidation of Dithiothreitol by Dissolved Oxygen in the Presence of Carbon Nanoparticles

Abstract: The catalytic nature of particulate matter is often advocated to explain its ability to generate reactive oxygen species, but quantitative data are lacking. We have performed molecular characterization of three different carbonaceous nanoparticles (NP) by: 1. identifying and quantifying their surface functional groups based on probe gas-particle titration; 2. studying the kinetics of dissolved oxygen consumption in the presence of suspended NP's and dithiothreitol (DTT). We show that these NP's can reversibly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…The main question remaining to be fully understood is which metallic species are the most soluble contributors to oxidative potential. Regarding the particulate insoluble fraction not discussed in this study, Sauvain and Rossi [71] evidenced that functional groups on carbon nanoparticle surfaces could reversibly change their oxidation state, confirming their catalytic nature and explaining their ability to generate reactive oxygen species. Likewise, Leclercq et al [72] demonstrated that the insoluble fraction of urban airborne fine particles (PM 2.5 ) could induce cytotoxicity while both soluble and insoluble particulate fractions could be linked to the secretion of cytokines.…”
Section: Introductionsupporting
confidence: 60%
“…The main question remaining to be fully understood is which metallic species are the most soluble contributors to oxidative potential. Regarding the particulate insoluble fraction not discussed in this study, Sauvain and Rossi [71] evidenced that functional groups on carbon nanoparticle surfaces could reversibly change their oxidation state, confirming their catalytic nature and explaining their ability to generate reactive oxygen species. Likewise, Leclercq et al [72] demonstrated that the insoluble fraction of urban airborne fine particles (PM 2.5 ) could induce cytotoxicity while both soluble and insoluble particulate fractions could be linked to the secretion of cytokines.…”
Section: Introductionsupporting
confidence: 60%
“…Saffari et al (2014a) reported that DTT activity was strongly associated with water‐soluble and water‐insoluble organics, hopanes, and even elemental carbon. In fact, dissolved oxygen caused interfacial catalytic oxidation of DTT in the presence of elemental carbon particles (Sauvain & Rossi, 2016). Verma et al (2015) reported the importance of humic‐like substances (HULIS) such as quinones and secondary organic aerosols in ambient OP, and Yu et al (2018) reported interactions of HULIS, and transition metals should be considered for the DTT activity.…”
Section: Introductionmentioning
confidence: 99%
“…C=C stretching is attributed to either aromatic compounds or microcrystalline structure of soot particles due to its polyaromatic character [52,53]. In both cases, the IR-inactive C=C mode is augmented by either sufficient asymmetry of the carbon material polyaromatic structure (e.g., by defects) or related to carbonyl groups conjugated with aromatic segments [54]. At 880 cm −1 carbonate CO 3 2− groups dominate.…”
Section: Ff-related Ftir Spectral Featuresmentioning
confidence: 99%